An Unknown Posthumous Eulogy to the Kievan Metropolitan Petro Mohyla in a Ukrainian Manuscript from the Late 17th Century as a Work by Lazar Baranovich - Temčinas, Sergejus (Slavistica Vilnensis, 2025)
The article introduces an unknown posthumous panegyric to the Kievan Metropolitan Peter Mohyla († 1647), contained in a Ukrainian Didactic Gospel manuscript copy from the late 17th century. After two panegyrics in Polish (Nagrobki... by Lazar Baranovich and Żal ponowiony... by Joseph Kalimon, both from 1647) and two later Ruthenian eulogies by Anthony Radivilovsky (dated 1656 and 1658), this is the fifth (though chronologically relatively early) posthumous panegyric to this Kievan Metropolitan. It is written in Church Slavonic and was probably delivered at the Kiev Brotherhood College (this information is contained in the title), apparently in 1647. Unfortunately, the text has been preserved quite fragmentarily (as only the title and a few opening lines have survived), but neverthless, it can be attributed to Lazar Baranovich who used to write his sermons in Church Slavonic with some Latinisms and Polonisms. In the academic year 1646/47, i.e., at the time of the death of Petro Mohyla, Baranovich was a professor of rhetoric at the Kievan Brotherhood College, which made him the most suitable person to write a posthumous eulogy on behalf of this educational institution. This eulogy should be considered in the history of Ukrainian Baroque literature. The article contains a complete publication of the preserved fragment.
Keywords: Slavic literature; Ukrainian manuscripts; Baroque; posthumous panegyrics; Church Slavonic writing; Peter Mohyla